Analysis of Revenue Recognition and Contract Cost Recognition under PSAK 72: Evidence from PT Wijaya Karya (Persero) Tbk Listed on the Indonesia Stock Exchange - Wahyuni; Miftahul Janna; Nurhalima; Lidia Arianti Agustin; Nurhalisa (www.amertainstitute.com, 2026)
This study aims to analyze the implementation of revenue recognition and construction contract cost recognition under PSAK 72 at PT Wijaya Karya (Persero) Tbk, one of Indonesia’s largest state-owned construction companies listed on the Indonesia Stock Exchange. The research evaluates whether the company’s accounting practices comply with the principles of PSAK 72 concerning revenue from contracts with customers, particularly in relation to performance obligations and the matching of contract costs with recognized revenue. A qualitative descriptive approach was employed using secondary data collected from annual reports, audited financial statements, and relevant academic literature. Data were analyzed through document analysis by comparing the company’s accounting policies with the recognition and measurement requirements stipulated in PSAK 72. The findings indicate that the adoption of PSAK 72 has not significantly altered revenue recognition practices for the company’s core construction projects, as revenue continues to be recognized over time using the cost-to-cost percentage-of-completion method, which is consistent with the standard. However, challenges remain in recognizing and classifying construction contract costs, particularly regarding the presentation of contract assets and inventories, indicating potential inconsistencies in applying the matching principle. These findings suggest that formal compliance with PSAK 72 in revenue recognition does not necessarily ensure equivalent compliance in contract cost recognition. This study contributes to the accounting literature by providing empirical evidence on PSAK 72 implementation in Indonesia’s construction industry and highlights the importance of strengthening internal controls, cost estimation procedures, and financial reporting quality to improve transparency and decision-making.